Coming of age under martial law : the initiation novels of Poland's last communist generation - Vasileva-Karagʹozova, Svetlana (Rochester studies in East and Central Europe, 2015)
"How do historical cataclysms affect the social conditioning of young people? How do individuals born in the same period come to form an identifiable "generation"? How do coming-of-age stories create a sense of community and generational identity? Coming of Age under Martial Law: The Initiation Novels of Poland's Last Communist Generation addresses these questions, examining a selection of post-1989 coming-of-age novels authored by the generation of Polish writers whose transition from adolescence to adulthood coincided with Poland's transition from communism to liberal democracy. Svetlana Vassileva-Karagyozova argues that when cataclysms of any nature overlap with the sensitive period of maturation into adulthood, they disrupt the natural rhythm of society's self-renewal. In the case of the Polish '89ers, the generational clash with their predecessors did not produce the anticipated generational change in leadership, but a pathological role reversal: the elders refused to give up their leadership positions, while the young were stifled in their development and occupied marginal social spaces"--